Maternal death due to COVID-19 - Hantoushzadeh, Sedigheh; Shamshirsaz, Alireza A.; Aleyasin, Ashraf; Seferovic, Maxim D.; Aski, Soudabeh Kazemi; Arian, Sara E.; Pooransari, Parichehr; Ghotbizadeh, Fahimeh; Aalipour, Soroush; Soleimani, Zahra; Naemi, Mahsa; Molaei, Behnaz; et al. (American journal of obstetrics and gynecology, 2020)
Despite 2.5 million infections and 169,000 deaths worldwide (as of April 20, 2020), no maternal deaths and only a few pregnant women afflicted with severe respiratory morbidity have been reported to be related to COVID-19 disease. Given the disproportionate burden of severe and fatal respiratory disease previously documented among pregnant women following other coronavirus-related outbreaks (SARS-CoV in 2003 and MERS-CoV in 2012) and influenza pandemics over the last century, the absence of reported maternal morbidity and mortality with COVID-19 disease is unexpected. To describe maternal and perinatal outcomes and death in a case series of pregnant women with COVID-19 disease. We describe here a multiinstitution adjudicated case series from Iran that includes 9 pregnant women diagnosed with severe COVID-19 disease in their second or third trimester. All 9 pregnant women received a diagnosis of SARS-CoV-2 infection by reverse transcription polymerase chain reaction nucleic acid testing. Outcomes of these women were compared with their familial/household members with contact to the affected patient on or after their symptom onset. All data were reported at death or after a minimum of 14 days from date of admission with COVID-19 disease. Among 9 pregnant women with severe COVID-19 disease, at the time of reporting, 7 of 9 died, 1 of 9 remains critically ill and ventilator dependent, and 1 of 9 recovered after prolonged hospitalization. We obtained self-verified familial/household cohort data in all 9 cases, and in each and every instance, maternal outcomes were more severe compared with outcomes of other high- and low-risk familial/household members (n=33 members for comparison). We report herein maternal deaths owing to COVID-19 disease. Until rigorously collected surveillance data emerge, it is prudent to be aware of the potential for maternal death among pregnant women diagnosed as having COVID-19 disease in their second or third trimester.